Silicon activity in liquid Fe-Co-Cu-Si - Banda, W.; Georgalli, G.; Eksteen, Jacques; Lang, C. (Maney Publishing, 2009)
The activity of silicon in the liquid Fe-Co-Cu-Si system was studied by chemical equilibration using a gas/silica/alloy technique at 1450°C. This was carried out in the compositional range relevant to the ferrocobalt alloy produced during slag cleaning of copper waste slags. The activity of silicon was investigated for the quaternary (Fe-Co-Cu-Si) system as well as the ternary subsystems. The results show a large negative deviation from ideal solution (Rauoltian) behaviour. The activity coefficient of silicon was found to be in the magnitude of 10-3. © 2009 Institute of Materials, Minerals and Mining and The AusIMM.